2021
DOI: 10.48550/arxiv.2106.04554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey of Transformers

Tianyang Lin,
Yuxin Wang,
Xiangyang Liu
et al.

Abstract: Transformers have achieved great success in many artificial intelligence fields, such as natural language processing, computer vision, and audio processing. Therefore, it is natural to attract lots of interest from academic and industry researchers. Up to the present, a great variety of Transformer variants (a.k.a. X-formers) have been proposed, however, a systematic and comprehensive literature review on these Transformer variants is still missing. In this survey, we provide a comprehensive review of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 112 publications
0
78
0
Order By: Relevance
“…Below, we briefly describe the core components behind the success of ViTs that are self-attention and multi-head selfattention. For a more in-depth analysis of numerous ViT architectures and applications, we refer interesting readers to the recent relevant survey papers [23], [81]- [84].…”
Section: Transformersmentioning
confidence: 99%
“…Below, we briefly describe the core components behind the success of ViTs that are self-attention and multi-head selfattention. For a more in-depth analysis of numerous ViT architectures and applications, we refer interesting readers to the recent relevant survey papers [23], [81]- [84].…”
Section: Transformersmentioning
confidence: 99%
“…Many attention-based models have been developed to improve the performance of classification and regression algorithms. Surveys of various attention-based models are available in [2,3,4,5,17,1].…”
Section: Related Workmentioning
confidence: 99%
“…Many attention-based models are also applied to the computer vision area, including image-based analysis, visual question answering, etc. Detailed surveys and reviews of attention, its forms, properties and applications can be found in [2,3,4,5,1].…”
Section: Introductionmentioning
confidence: 99%
“…There are many other variables in the robustness landscape such as embedding technique, robustness metrics, and robustness techniques which were not covered under their survey. Lin et al [29] presented a research survey on transformers which are pre-trained NLP models. The study is centered around robustness from a model stand point where learning models such as BERT and RoBERTa can contribute to robustness.…”
Section: Related Workmentioning
confidence: 99%